2010
DOI: 10.1194/jlr.m000513
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant lipids regulate LPS-induced interleukin-8 production in A549 lung epithelial cells by inhibiting translocation of TLR4 into lipid raft domains

Abstract: Supplementary key words lipopolysaccharide • cytokines • infl a mmationAs a primary interface between the lung and pathogens, the epithelial cells lining the airways and the alveoli are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 67 publications
(82 reference statements)
1
52
1
Order By: Relevance
“…It was recently shown that LPS treatment induced activation of TLR4 via its translocation into membrane lipid raft microdomains, and this translocation was inhibited by incubation of the cells with the surfactant lipid. Lipid-mediated inhibition of TLR4 membrane repartition can downregulate the synthesis of IL-8 by an alveolar epithelial cell line in response to LPS (1,49). This recent finding gives rise to the hypothesis that D2S membrane activity may result in rearrangement of lipid packing after D2S membrane insertion, which will interfere with TLR membrane repartition.…”
Section: Discussionmentioning
confidence: 94%
“…It was recently shown that LPS treatment induced activation of TLR4 via its translocation into membrane lipid raft microdomains, and this translocation was inhibited by incubation of the cells with the surfactant lipid. Lipid-mediated inhibition of TLR4 membrane repartition can downregulate the synthesis of IL-8 by an alveolar epithelial cell line in response to LPS (1,49). This recent finding gives rise to the hypothesis that D2S membrane activity may result in rearrangement of lipid packing after D2S membrane insertion, which will interfere with TLR membrane repartition.…”
Section: Discussionmentioning
confidence: 94%
“…In the current study, phospholipid vesicles comprised of the surfactant phospholipids dipalmitoylphosphatidylcholine, dipalmitoyl oleoyl-phosphatidylcholine did not reduce the LPS activation of TLR4 signaling, indicating that these two abundant surfactant phospholipid species do not independently exert anti-inflammatory activity. In a separate study, Survanta was shown to inhibit LPS signaling in vitro by blocking translocation of TLR4 to lipid rafts in A549 cells (34). Future studies will determine if SP-C reconstituted with defined lipids redirects TLR4 localization in response to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors (TLRs) recognize highly conserved structural motifs from either pathogens or damaged and stressed tissues and are involved in microglial response to physiological and pathological signals. TLR4, in particular, reportedly mediates neuroprotective (1,2) and neurotoxic (3)(4)(5) effects, suggesting that TLR4 activation needs to be tightly controlled, to regulate the switch between its different roles in immune surveillance or neuroinflammatory propagation.…”
Section: Introductionmentioning
confidence: 99%